PENINGKATKAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN STRATEGI PROBLEM BASED LEARNING DI SMK NEGERI 1 BUNGO - nicolas junibinsar simatupang (Jurnal Tunas Pendidikan, 2022)
The background of this research is the low learning outcomes of mathematics subjects class XII Ak Muara Bungo. The causative factor is that learning is still conventional, there is no student involvement in the learning process, not using Problem Based Learning strategies in the learning process. This research is a class action research with qualitative and quantitative approaches. The subjects of the study were class XII students of Ak Muara Bungo which numbered 30 students. In its implementation, this study consists of 2 cycles carried out by researchers. Each cycle consists of 4 stages, namely action planning activities, action implementation, observation, and reflection on each cycle. The data of this study were collected based on observations, learning outcomes tests, and documentation. The results showed that 1) the application of Problem Based Learning strategies can improve the results of teacher and student activities. Teacher activities in cycle I by 81% (good category) in cycle II increased to 91% (very good category). Student activities in cycle I by 84% (good category) in cycle II increased to 90% (very good category). 2) Improvement in learning outcomes that achieve grades above KKM (65) with a pre-cycle percentage of 57%, cycle I 60%, and cycle II 76%.